CERMIN SOSIAL TERHADAP KEBEBASAN PEREMPUAN PADA MASYARAKAT REFORMASI DALAM NOVEL SAMAN KARYA AYU UTAMI - Hidayat, Dear Dirgahayu; Dwi Susanto (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
The novel Saman, written by Ayu Utami, is the result of reflection and response to the social conditions of Indonesian society in the 1998 reform era, especially in the context of women’s liberation. This study uses a sociology of literature approach to the social response of the Saman text to social conditions in the post-New Order era. The research data was obtained from the contents of the novel text and the author’s biography. The primary data source used is the novel Saman (1998) by Ayu Utami. This study examines various issues, including Ayu Utami’s sociological background, the social conditions when the work was published, the ideas contained in the novel, and the reflection of society incorporated in Saman’s novel. The results of this study indicate that Ayu Utami is a representative of a society that longs for equality for women and reflects the social situation in 1998. The concordance between the author’s sociological background, social conditions at the time of publication of the work, and the thematic ideas in the novel indicate that Ayu’s novel Saman Utami reflects community life, especially women, in the 1990s.